Mejora a los procesos de gestión del claustro del macroproceso de formación de la ESPAM MFL - Párraga Zambrano, Jennifer Lorena (2020)
The present degree work was aimed at improving the management processes of the cloister at ESPAM MFL training macroprocess with the aim of achieving efficiency. The methodology used was based on two analyzes: the first, through techniques such as observation, interview, and focus group; the second, by applying Value Added Analysis (AVA) to processes; and finally, the proposal for improvements to the stakeholders was socialized. All these research actions allowed us to reach the following conclusions: there are inefficiencies in the documentation and survey of the processes according to the regulations studied and the experience of the experts, so new processes were redesigned in accordance with the current provisions issued by the Higher Education Quality Assurance Council (CACES); likewise, it was evident that, of the selected processes of the cloister management, the activities are mostly of preparation and movement, that is, they do not add value, and therefore, with low efficiency, proposing for these criteria of decision like the integration and the automation of the activities; discernments that were taken into account for the proposal, and sent to the Academic and Research Vice-Rector's Office and to the Quality Management Department, to publicize the improvements incorporated into the cloister management processes.